2018
DOI: 10.1371/journal.pone.0192075
|View full text |Cite
|
Sign up to set email alerts
|

Model selection and averaging in the assessment of the drivers of household food waste to reduce the probability of false positives

Abstract: Food waste from households contributes the greatest proportion to total food waste in developed countries. Therefore, food waste reduction requires an understanding of the socio-economic (contextual and behavioural) factors that lead to its generation within the household. Addressing such a complex subject calls for sound methodological approaches that until now have been conditioned by the large number of factors involved in waste generation, by the lack of a recognised definition, and by limited available da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…This database included statistics regarding objective amount of avoidable household food waste (the terms 'avoidable food waste', 'food waste', and 'food wastage' are being used alternately throughout the paper to describe edible, avoidable food discarded by households) (kg per household; measured through a physical waste survey), sociodemographic factors (gender, household age structure, household size, household composition, home ownership status, type of residence, local authority, presence of children, employment status, and socioeconomic status), and behavioral variables (meal preplanning, pre-shopping cupboard checking, preparing a shopping list, using leftovers, food storage practices, type and frequency of shopping trips, and presence of fussy eaters). Household size, the presence of fussy eaters, employment status, home ownership status, and the local authority were all identified as main drivers of food waste [15]. Grainger et al [15] found no significant effect of any of the behavioral factors on measured amount of food waste.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…This database included statistics regarding objective amount of avoidable household food waste (the terms 'avoidable food waste', 'food waste', and 'food wastage' are being used alternately throughout the paper to describe edible, avoidable food discarded by households) (kg per household; measured through a physical waste survey), sociodemographic factors (gender, household age structure, household size, household composition, home ownership status, type of residence, local authority, presence of children, employment status, and socioeconomic status), and behavioral variables (meal preplanning, pre-shopping cupboard checking, preparing a shopping list, using leftovers, food storage practices, type and frequency of shopping trips, and presence of fussy eaters). Household size, the presence of fussy eaters, employment status, home ownership status, and the local authority were all identified as main drivers of food waste [15]. Grainger et al [15] found no significant effect of any of the behavioral factors on measured amount of food waste.…”
Section: Introductionmentioning
confidence: 97%
“…Household size, the presence of fussy eaters, employment status, home ownership status, and the local authority were all identified as main drivers of food waste [15]. Grainger et al [15] found no significant effect of any of the behavioral factors on measured amount of food waste.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations